Pseudobankesia lichenaria spec. nov., eine neue Psychiden-Art aus der Zagoria im griechischen Voria Pindos-Gebirge (Lepidoptera: Psychidae). - Weidlich, Michael (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Pseudobankesia spec. nov. from the Zagoria is described. Informations on their biology and ecology are reported. The species live very hidden in cracks at rocks. Furthermore, an overview on the Pseudobankesia species distributed to the Balkans is given.KeywordsGreece, Voria Pindos, Zagoria, Pseudobankesia lichenaria spec. nov., Psychidae, Lepidoptera.Nomenclatural Actslichenaria Weidlich, 2016 (Pseudobankesia), spec. n.